Forum internum: Überlegungen zum protestantischen Gewissensbegriff - Barth, Roderich (Evangelische Theologie, 2023)
While the previous contributions focus on historic and present forms of the biblical concept of a judging God this paper highlights the perspective of the religious subject. The plausibility of the motif of a divine judge and the causes of the "fading away" of this concept in the present will be unfolded within the framework of the concept of consciousness. On the basis of a pop-cultural case study, some light is thrown on the history of the concept and its emphasis in Luther's theology before an appreciation of its reformulation in Kant's philosophy of religion is possible. Conscience in all its facets undoubtedly also exists in profane form, notwithstanding it offers points of contact for articulation in the medium of religious symbolic worlds.